On the Planckian bound for heat diffusion in insulators - Mousatov, Connie H.; Hartnoll, Sean A. (Nature physics, 2020)
In an insulator, thermal transport at high temperature is expected to be dominated by entirely classical phonon dynamics. In apparent tension with this expectation, recent experimental observations have led to the conjecture that the transport lifetime, τ , is subject to a Planckian bound from below, namely, τ ≳ τ Pl ≡ ℏ ∕ ( k B T ). Here, we argue that this Planckian bound is due to a quantum-mechanical bound on the sound velocity: v s < v M . The ‘melting velocity’ v M is defined in terms of the melting temperature of the crystal, the interatomic spacing and Planck’s constant. We show that for several classes of insulating crystals, both simple and complex, τ ∕ τ Pl ≈ v M ∕ v s at high temperatures. The velocity bound therefore implies the Planckian bound. At high temperature, the heat diffusion in an insulator is expected to be dominated by entirely classical phonon dynamics. But theoretical study shows that the transport lifetime is subject to a quantum-mechanical bound related to the sound velocity.